The Radical Thought And Autobiography In American Literature - Mihoubi, Houria (Université de M'sila, 2014)
Autobiography as a literary genre isan account of a person's life written by him. obviously an autobiography runs the danger of being highly subjective since it is confined to the author’s life, experiences, and world view. In autobiography, the author often finds an opportunity to express his own thought that can be radical.The first purpose of the article is to treat the radical thought through four American autobiographies: Frederick Douglass The Life of F. Douglass, Richard Wright’s Black Boy, Mary Grow Dog’s Lakota Women, and Henry David Thoreau’s Walden. The other objective is to shed light on how these writers tried, by narrating their lives, to convey to the reader of their radical views of society and therefore, sought to foster social reform. Frederick Douglas and Richard Wright wrote to defend and argue for abolitionism, Mary Grow Dog wrote to ask for a better place for the American Indian women in the American society, while Henry David Thoreau defended environmentalism as a philosophy of life. يهدف المقال إلى تسليط الضوء على العلاقة بين السيرة الذاتية كنتاج أدبي والفكر الراديكالي كسبب للتغبير الاجتماعي و ذلك في الأدب الأمريكي. لدراسة هذه العلاقة، رأينا أن يرتكز المقال على أربع سير ذاتية لكتاب أمريكيين و هم "السيرة الذاتية لفريديرك دوغلاس" لفريديرك دوغلاس، "الطفل الاسود" لريتشرد رايت، "إمرأة لاكوتا" لماري كرو دوق و"والدن" لهنري ديفد ثورو. في كل واحدة من السير المذكورة يطرح الكاتب فكرة راديكالية من خلال سرد تجاربه معطيا تبريرات لهذه الفكرة فدوغلاس و رايت دافعا عن حقوق السود في اتمع الأمريكي ذو الأغلبية البيضاء ماري كرو دوق دافعت عن حقوق المرأة الهندية في اتمع الأمريكي و ثورو طرح ما يدعى اليوم بالبيئية. نخلص في بحثنا إلى أن السيرة الذاتية يمكن أن تكون مناخا أدبيا مناسبا لطرح الفكر الأيديولوجي
Keywords: Radicalism, autobiography, abolitionism, women, Environmentalism.